Correlation of Smoking Behavior with Body Mass Index (BMI) in Palm Oil Mill Workers - Yuziani; Rizka Sofia; Harvina Sawitri (LPPM Universitas Malikussaleh, 2022)
The Smokers tend to weigh less than never smokers, while successful quitting leads to an increase in body weight. Because smokers and non-smokers may differ in genetic and environmental family background, we analysed data from twin pairs in which the co-twins differed by their smoking behaviour to evaluate if the association between smoking and body mass index (BMI) remains after controlling for family background. The research will be carried out at the palm oil mill of PT. Syaukath Sejahtera, Bireuen Regency. Sampling was carried out by means of simple random sampling on selected subjects using a cross-sectional design. . The end result of this study is smoking is associated with lower BMI and smoking cessation with higher BMI.